2015
DOI: 10.1039/c4ay02118e
|View full text |Cite
|
Sign up to set email alerts
|

A novel on-line ultrasonic extraction system for determination of the optimal ultrasonic frequency for plant material

Abstract: The novel extraction system was developed to efficiently extract plant material by determining optimum extraction frequency via two steps. Extraction experiments show that this extraction system gave a higher extraction yield compared to existing ultrasonic extraction method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Optimized conditions for ultrasonic extraction of hesperidin from tangerine peels were reported elsewhere. 35 The ultrasound frequency used in this study was in the range of 38 -42 kHz, which was similar to the optimized value in the earlier report. 35 The data set was subjected to the outlier tests, including Cochran test, single Grubbs test, and paired Grubbs test.…”
Section: Inter-laboratory Reproducibilitysupporting
confidence: 77%
“…Optimized conditions for ultrasonic extraction of hesperidin from tangerine peels were reported elsewhere. 35 The ultrasound frequency used in this study was in the range of 38 -42 kHz, which was similar to the optimized value in the earlier report. 35 The data set was subjected to the outlier tests, including Cochran test, single Grubbs test, and paired Grubbs test.…”
Section: Inter-laboratory Reproducibilitysupporting
confidence: 77%
“…For benefits of each frequency range for classes of compounds or applications, past literatures have evaluated the ultrasound frequency that delivers high targeted components recovery yields during ultrasound-assisted extraction from natural materials [15][16][17][18]19,20], notably studies on UAE of rutin from different natural materials [7,21]. However, those ultrasound frequencies were empirically selected from ultrasonic apparatuses or devices.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that the frequency of 55 kHz was an optimal ultrasonic frequency for the extraction of glycyrrhizic acid. Similarly, our previous studies [34,35] also reported that the highest extraction yield was obtained at an optimal ultrasonic frequency during the extraction of rutin from Sophora japonica and hesperidin from tangerine peels. These results were mainly attributed to the resonance mechanism of cavitation bubbles generated by ultrasound.…”
Section: Effect Of Ultrasonic Frequencymentioning
confidence: 97%
“…Secondly, the effect of ultrasonic frequency on the extraction yield of glycyrrhizic acid was performed at 25 • C, and ultrasound power of 125 W with different frequencies (20,30,40,55, and 90 kHz). Finally, the effect of extraction temperature on the extraction yield of glycyrrhizic acid was carried out at an ultrasonic frequency of 55 kHz and power of 125 W with different extraction temperatures (20,25,35,60, and 70 • C). The extraction process was repeated three times for each experiment.…”
Section: Single Factor Experimental Designmentioning
confidence: 99%